Optimalisasi Kegiatan Sosial dan Keagamaan di Desa Muara Laung II Melalui Kuliah Kerja Nyata Pengabdian Masyarakat - Natasya Audia Safitri; Siti Nurrahmah; Salahudin Salahudin; Ibnu Sina; Resti Restika; Yesa Susanti; Ahmad Fadillah Maulana; Isra Misra (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Real work lecture is one of the activities that aims to increase student participation in assisting community development, especially in the social and religious fields. This article discusses efforts to optimize social and religious activities in Muara Laung II Village through the KKN program. This activity involves students in various work programs and religious guidance in accordance with the needs of the local community. The results of this program show an increase in community participation in social and religious activities, an improvement in the quality of life, and an awareness of the importance of developing local potential. Optimization of this activity is expected to become a sustainable model of village community empowerment, with a positive impact on the social and spiritual welfare of the Muara Laung II community.